Magnesium Extraction of Ferronickel Slag Waste Processed by Alkali Fusion and Hydrochloric Acid Leaching - Prasetyo, Agus Budi; Azmi, Kaerul; Mayangsari, Wahyu; Febriana, Eni; Maksum, Ahmad; Juniarsih, Andini; Firdiyono, Florentinus; Soedarsono, Johny Wahyuadi (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
A research based on ferronickel slag has been carried out. The main compositions of ferronickel slag are silica, magnesium, iron, and aluminum in any oxide forms. Minor elements found in the ferronickel slag are nickel, chrome, cobalt, titanium and other elements. The ferronickel slag contains 41% of silica, 26.6% of magnesium and about 21% of iron. It shows that the ferronickel slag could be processed by pulling out its magnesium, so it would have a higher economic value. The ferronickel slag processing technology with alkali fusion and hydrometallurgy leaching method with acids areconsidered to be able to extract magnesium to be more economical in value. The objective of this research is to examine the solution concentration effect and temperatures so thatthe highest contents of magnesium can be obtained during the leaching process. This research used variations of 2M; 4M; 6M; and 8M concentrations; it also used variations in room temperature at 60°C and 80°C. The leaching process was carried out at 15; 30; 60; 120; and 240 minutes. Analyses of XRF, XRD, SEM, and ICP-OES were undertaken to see the characteristics of slags and magnesium content after the leaching process. The result showed that the highest magnesium extraction percentage was 82.67% at 80°C with a 2M solution concentration for 30 minutes. Kinetics studies exhibited that the magnesium leaching process of nickel slag is affected by diffusion and chemical reactions.
Keywords: Ferronickel Slag, Alkali Fusion, Leaching, Hydrochloric Acid, Magnesium, Percent of Extraction